Innovative Economy and Adult Education - Skwarek, Janusz; Łygas, Andrzej (Regional Barometer. Analyses & Prognoses, 2013)
This paper concerns important issues connected with adult continuing education in the context of innovative activity in a modern economy. The progress of civilization in the world leads to the creation of new goals and objectives in the entire system of education, and in particular in adult education. Education and the professional training of workers are closely connected with the development of companies and enterprises. Innovative activities contribute to the development of new technological and organizational solutions and to their popularization, creating and storing knowledge and abilities. The main elements in the sphere of the creation and popularization of innovation are: academic and applied sciences, companies, business environments, government institutions, corporations and international organizations.